99mTc-Pyrophosphate Retention in Atelectatic Pulmonary Tissues of a Patient With Transthyretin Cardiac Amyloidosis. (October 2021) - Pan, Yu; Wang, Yue; Zhou, Yilei; Xi, Yun; Zhang, Yifan
Abstract : Abstract: A 61-year-old man was hospitalized for suspected cardiac amyloidosis. 99m Tc-Pyrophosphate scintigraphy showed intense radiotracer uptake in the heart compared with the ribs, suggestive of transthyretin cardiac amyloidosis. Subsequent genetic test showed missense mutations in the transthyretin gene, which confirmed the diagnosis. Incidentally, a regional radiotracer uptake was seen in the bilateral lungs, respectively, corresponding to areas of atelectasis on the localizing CT of the SPECT/CT. Attention should be paid to radiotracer retention in lung atelectasis as it influences the H/CL (heart–to–contralateral lung) ratio calculation and may hinder the diagnosis of cardiac amyloidosis based on the quantitative H/CL ratio.